The Era of Kilometer-Scale Neutrino Detectors - Francis Halzen; Uli Katz (Advances in High Energy Physics)
Neutrino astronomy beyond the Sun was first imagined in the late 1950s; by the 1970s, it was realized that kilometer-scale neutrino detectors were required. The first such instrument, IceCube, transforms a cubic kilometer of deep and ultra-transparent Antarctic ice into a particle detector. KM3NeT, an instrument that aims to exploit several cubic kilometers of the deep Mediterranean sea as its detector medium, is in its final design stages. The scientific missions of these instruments include searching for sources of cosmic rays and for dark matter, observing Galactic supernova explosions, and studying the neutrinos themselves. Identifying the accelerators that produce Galactic and extragalactic cosmic rays has been a priority mission of several generations of high-energy gamma-ray and neutrino telescopes; success has been elusive so far. Detecting the gamma-ray and neutrino fluxes associated with cosmic rays reaches a new watershed with the completion of IceCube, the first neutrino detector with sensitivity to the anticipated fluxes. In this paper, we will first revisit the rationale for constructing kilometer-scale neutrino detectors. We will subsequently recall the methods for determining the arrival direction, energy and flavor of neutrinos, and will subsequently describe the architecture of the IceCube and KM3NeT detectors.